PENGARUH KESADARAN WAJIB PAJAK, TINGKAT PEMAHAMAN WAJIB PAJAK, PELAYANAN FISKUS DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (Studi Empiris Pada Pengusaha UMKM di KPP Pratama Senapelan) - Lidya Puspitasari; Zirman -; Rusli - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the effect caused by the variable taxpayer awareness, level of understanding of the taxpayer's, the service tax authorities and tax penalties on tax compliance. This study used purposive sampling with 86 samples obtained from the calculation formula slovin. Data collection techniques in this study is in the form of questionnaires, while data analysis technique used is multiple regression analysis were processed with SPSS version 17 for Windows. From the results of the testing that has been done, simultaneous regression test (F test) showed that all independent variables studied have a simultaneous effect on the variable tax compliance. Partial regression test (t test) showed that all independent variables studied partial effect on the variable tax compliance. The magnitude of the effect caused by Adjusted R2 by four variables together against the dependent variable 54.7%, while the remaining 45.3% is influenced by other variables not examined in this study.Keywords: taxpayer awareness, level of understanding of the taxpayer's, the service tax authorities and tax penalties, tax compliance